Profile of Problem-Solving Ability of High School Students with Different Class Classifications on Light Wave Learning Topic - Ahmad Nasich Luthfi; Edi Supriana; Supriyono Koes Handayanto (Pascasarjana Universitas Negeri Malang (UM), 2021)
Abstract: The purpose of the study is to compare senior high school problem-solving abilities with different class classifications on light waves. The study used a survey method with subjects of class XI as many as 123 high school students in Mojokerto. The instrument used is in the form of problem-solving abilities items as many as six questions. Student approaches to items are categorized into five: scientific approach, plug & chug (structured and unstructured), memory-based approach, and no clear approach. The results of the study showed that students' problem-solving abilities were in the plug & chug (structured and unstructured), and memory-based approach. This shows if students are still in the novice group. The highest percentage of problem-solving abilities is students of class XI and the lowest is students of class XI. This research needs to be followed up with various efforts to overcome the low problems solving abilities of students in physics learning.Abstrak: Penelitian bertujuan mengkomparasikan kemampuan pemecahan masalah sswa SMA dengan klasifikasi kelas berbeda pada gelombang cahaya. Peneltian mengunakan metode survey degan subjek siswa kelas XI sebanyak 123 siswa SMA di wlayah Mojokerto. Instrument yang dgunakan berupa butir soal kemampuan pemecahan masalah gelombang cahaya sebanyak 6 soal. Pendekatan siswa tehadap butir soal dkategorikan menjadi lima, yaitu: scientific approach, plug & chug terstruktur dan tidak terstruktur, memory based approach serta no clear approach. Hasil peneltian menujukkan bahwa kemapuan pemecahan masallah siswa berada pada pendkatan Plug & Clug terstruktur, tidak terstruktur dan pendekatan memory based approach. Hal tersebut menunjukkan jika siswa masih berada pada kelompok novice. Persentase kemampuan pemecahan masalah paling tinggi adalah siswa kelas XI dan terendah adalah siswa kelas XI. Penelitian ini perlu ditindaklanjuti dengan berbagai upaya untuk mengatasi redahnya kmampuan pmecahan masalah siswa dalam pebelajaran fisika.